KEBIJAKAN PEMERINTAH KOTA SEMARANG DALAM PEMANFAATAN ASET TANAH UNTUK PEMBANGUNAN - Fareed Aziiz Al-Lathiif, Ana Silviana (Fakultas Hukum, Universitas Diponegoro, 2018)
Policy is a series of concepts and principles that become guidelines and the basis of plans in carrying out a job, leadership, and how to act. Local governments in empowering assets owned in particular land can be carried out in several methods, namely through leasing, borrowing, KSP, BGS or BSG, and KSPL. Semarang City in utilizing land assets can determine policies that can provide benefits to local governments, including in the construction of facilities and infrastructure in this case is cooperation with investors in development. This research is to find out about the form of utilization of regional assets in the form of land with investors in the construction of Hotel Tentrem in the City of Semarang, and legal protection for the surrounding community with the construction of the Hotel. The research method used in this study through an empirical juridical approach, by digging data through primary data obtained from field research and secondary data obtained by document studies. The collected data will be analyzed qualitatively to answer the problem of this research. The results showed that the policy of the Semarang city government in the utilization of land assets was related to the development of Hotel Tentrem through a mechanism for a timed rental system, and legal protection obtained by the surrounding community towards the construction of hotel tents through investor CSR. Keywords: Utilization of regional assets, regional government policies, land rights